The Effects of SKT2 Meditation with Diet Control Knowledge on Ischemic Heart Disease Preventive Behaviors of Hypertensive Patients - ์Wongtrakool, Natgrita; Tongvichean, Sulee; Supremsri, Sararak (Journal of The Royal Thai Army Nurses, 2021)
The objective of this quasi-experimental research with a control group was to study the effects of SKT2 meditation practice with diet control knowledge on ischemic heart disease preventive behavior in hypertensive patients. The subjects were 24 hypertensive patients, divided into experimental and control groups. The experimental instruments were 1). SKT2 meditation practice manual and diet education accordance with the DASH Diet. 2) data collection tools were 4 parts questionnaire 2.1) personal information 2.2) perceived severity 2.3) perceived susceptibility, and 2.4) preventive behaviors of ischemic heart disease. Both of them had been validated by 3 experts. The CVI value were between 0.67-1.00, while the reliability of part 2-4 questionnaires which tryout in a similar group of 30 hypertensive patients were at 0.88, 0.88, and 0.82, respectively. The statistics used were percentage, mean, standard deviation and t-test. The results showed that 1) the mean score of perceived severity, perceived susceptibility, and the preventive behaviors after the intervention program of the experimental group were higher than before experiment with significantly different at the 0.001 level. 2) The average blood pressure after the experiment of the experimental group was decreased more than the control group with statistical significance at the .001 level, whereas the control group were not different.